Determination of biomarkers for toxicity and antiretroviral adherence in hair in South African patients - Johnston, Jenna (Division of Clinical Pharmacology, 2018)
Background: Substance abuse is one of the many factors associated with poor levels of antiretroviral adherence and is also prevalent among HIV-infected individuals. Ethyl glucuronide, a minor metabolite of alcohol, is a stable biomarker in hair that can be used to detect and monitor alcohol consumption over long time periods. Drugs of abuse are also detected in hair. Hair provides a longer window of drug detection compared to blood and urine. Recently, hair has also been studied as an alternative matrix for adherence monitoring and concentrations of antiretrovirals in hair have been shown to be closely correlated with virologic outcomes. This study investigated the impact of substance abuse on adherence among HIV-infected patients attending an antiretroviral therapy clinic in Cape Town by measuring drug concentrations in hair. Efavirenz levels in hair were also measured to investigate the usefulness of using hair analysis as a method of adherence monitoring within the South African context. Method: This study describes the development and validation of three liquid chromatography tandem mass spectrometry methods of hair analysis. The first method developed was for the quantification of ethyl glucuronide in 20 mg samples of hair. This method was validated over the calibration range 7.5 - 480 pg/mg. Secondly, a qualitative method was developed to screen hair samples for amphetamine, methamphetamine, cocaine, benzoylecgonine, cocaethylene and methaqualone. The final method developed was for the quantification of efavirenz in 0.2 mg samples of hair. This method was validated over the calibration range 0.625 - 40 ng/mg. The validated methods were applied to 257 samples of hair collected from 135 HIV-infected patients during visits to the clinic at weeks 16, 32 and 48. The results generated from the analysis of the hair samples were analysed in the context of additional adherence measurements collected for a related randomized controlled study. Results: Analysis of the hair samples for ethyl glucuronide demonstrated that 27% of the samples analysed contained levels above 30 pg/mg which is the cutoff value suggested by the Society of Hair Testing to identify heavy drinkers. The results also show limitations to using the CAGE alcohol abuse screening tool which had a poor sensitivity of only 28.8%. Eight (5.9%) out of the 135 participants were identified to be chronic drug users, and of these five (62.5%) were identified to be heavy drinkers as well. The most commonly abused drug identified in the screen was methaqualone. The median efavirenz levels at weeks 16, 32 and 48 were 5.52 ng/mg (IQR: 3.60 - 9.77), 5.75 ng/mg (IQR: 3.21 - 8.18) and 4.89 ng/mg (IQR: 3.10 - 7.94) respectively. Participants with the poor CYP2B6 metaboliser genotype had significantly higher median efavirenz hair concentrations compared to participants with intermediate and extensive genotypes (P < 0.0001). Efavirenz levels in hair and plasma samples were strongly correlated throughout the study (Spearman correlation coefficients: 0.672 - 0.741, all P values < 0.0001). Substance abuse had no impact on adherence measured by an electronic adherence monitoring device. No significant correlation was observed between adherence and levels of efavirenz in hair. Conclusions: Methods of hair analysis were developed and successfully applied to hair samples in the context of better understanding the impact of substance abuse on adherence. The results from the analysis of the hair samples provided insight into the prevalence of substance abuse among HIV-infected patients. The strong correlation observed between levels of efavirenz in hair and plasma suggest that, in this subset of HIV-infected patients, a single plasma concentration was as good an adherence measure as a hair concentration. The hair analysis methods developed and validated in this study are novel in South Africa and demonstrate the potential of this matrix to be used in various contexts within the country.